Evaluation of the efficacy of a commercial inactivated genogroup 2b-based porcine epidemic diarrhea virus (PEDV) vaccine and experimental live genogroup 1b exposure against 2b challenge - Tanja Opriessnig; Priscilla F. Gerber; Huigang Shen; Alessandra Marnie M. G. de Castro; Jianqiang Zhang; Qi Chen; Patrick Halbur (Veterinary Research, 2017)
Abstract Porcine epidemic diarrhea virus strains from the G1b cluster are considered less pathogenic compared to the G2b cluster. The aim of this study was to compare the ability of G1b-based live virus exposure against use of a commercial G2b–based inactivated vaccine to protect growing pigs against G2b challenge. Thirty-nine PEDV naïve pigs were randomly divided into five groups: EXP-IM-1b (intramuscular G1b exposure; G2b challenge), EXP-ORAL-1b (oral G1b exposure; G2b challenge), VAC-IM-2b (intramuscular commercial inactivated G2b vaccination; G2b challenge), POS-CONTROL (sham-vaccination; G2b challenge) and NEG-CONTROL (sham-vaccination; sham-challenge). Pigs were vaccinated/exposed at 3 weeks of age (day post-vaccination 0, dpv 0), VAC-IM-2b pigs were revaccinated at dpv 14, and the pigs were challenged at dpv 28. Among all groups, VAC-IM-2b pigs had significantly higher anti-PEDV IgG levels on dpv 21 and 28 while EXP-ORAL-1b pigs had significantly higher anti-PEDV IgA levels on dpv 14, 21, 28 and 35. EXP-ORAL-1b also had detectable IgA in feces. Intramuscular PEDV exposure did not result in a detectable antibody response in EXP-IM-1b pigs. The fecal PEDV RNA levels in VAC-IM-2b pigs were significantly lower 5–7 days after challenge compared to the POS-CONTROL group. Under the study conditions a commercial inactivated G2b-based vaccine protected pigs against G2b challenge, as evidenced by reduction of PEDV RNA in feces for 3–4 logs during peak shedding and a shorter viral shedding duration. The oral, but not the intramuscular, experimental G1b-based live virus exposure induced a high anti-PEDV IgA response prior to challenge, which apparently did not impact PEDV shedding compared to POS-CONTROL pigs.